Hyperglycemia, oxidative stress, and the diaphragm: a link between chronic co-morbidity and acute stress? - Hafner, Sebastian (BioMed Central, 2014)
It is well established that prolonged, controlled mechanical ventilation is associated with contractile dysfunction of the diaphragm due to impaired function of the mitochondrial respiratory chain as a result of aggravated oxidative and nitrosative stress. Sepsis and circulatory failure induce a similar response pattern. Callahan and Supinski now show that streptozotocin-induced insulin-dependent diabetes causes a comparable response pattern, both with respect to function and physiology - that is, reduced fiber force and, consequently, muscle contractility - but also as far as the underlying mechanisms are concerned. In other words, the authors elegantly demonstrate that the consequences of a chronic metabolic disease and that of acute critical illness may lead to the same phenotype response. It remains to be elucidated whether the underlying co-morbidity (for example, diabetes) adds to or even synergistically enhances the effect of an acute stress situation (for example, sepsis, mechanical ventilation). In addition, extending their previous work during shock states, the authors also show that administration of a preparation of the enzymatic anti-oxidant superoxide dismutase can reverse the deleterious effects of diabetes. These data are discussed in the context of the fundamental role of hyperglycemia in relation to metabolism-dependent formation of reactive oxygen species.